Covid-19, Congregational Worship, and Contestation over ‘Correct’ Islam in South Africa - Goolam Vahed (Journal for the Study of Religion)
In response to the global Coronavirus pandemic, South African President, Cyril Ramaphosa declared a national lockdown on March 26, 2020, which suspended, among other things, congregational worship. A group of Muslims made an urgent court application for permission to pray in mosques, which was dismissed on April 30, 2020, with the judiciary weighing in on the side of the public health good. This struggle over congregational prayers brought into the open, differences among Muslims in South Africa that have been simmering for several decades and raised questions as to how to balance the post-apartheid Constitution’s accommodation of religious practices with the needs of a secular state[1]. Conversely, what should Muslims do when they are required to follow the secular rules of a non-Muslim country that contradict their obligations to the tenets of their faith? The court case underlined the deep divides amongst Muslims and the changing structures of authority. In the absence of a central doctrinal authority the Ulama terrain is highly com-petitive and fraught with antagonistic doctrinal differences. It remains to be seen whether these divisions will boil over into physical confrontation among Muslims, and, with trust in the state dissipating, how Muslims will manage their relationship with the secular state.